Chromosomal description of three Dixonius (Squamata, Gekkonidae) from Thailand - Patawang I. (2023)
Chromosomal characteristics and karyological analysis of three Dixonius, including D. hangseesom, D. siamensis and D. melanostictus, from Thailand were stud-ied. Chromosome preparations were conducted by squash technique from bone marrow and testis. Conventional Giemsa’s staining and Ag-NOR banding techniques were applied to stain the chromosome. The results showed that the diploid chromosomes are 2n=40, for D. hangseesom and D. siamensis; and 2n=42, for D. melanostictus. The fun-damental number (NF) is 42 in D. hangseesom and D. siamensis and 44 in D. melanos-tictus. The types of chromosomes were 2 metacentrics and 38 telocentrics for D. hang-seesom and D. siamensis, while the karyotype of D. melanostictus comprised 2 acrocen-trics and 40 telocentrics. In the D. hangseesom and D. siamensis, NORs are located to the near centromere on long arm of the telocentric chromosome pair 13. Although, the NORs of D. melanostictus are situated on the subtelomeric region of telocentric chromosome pair 8. There are no sex differences in karyotypes between males and females of these three geckos species. We found that during metaphase I and metaphase II on male meiosis of the D. hangseesom and D. siamensis, the homologous chromosomes showed synapsis of 20 bivalents and 20 haploid chromosomes (n=20). Moreover, meta-phase I and metaphase II of the male D. melanostictus showed synapsis of 21 bivalents and 21 haploid chromosomes (n=21). Their karyotype formulas is as follows: D. hang-seesom (2n=40): Lm2 + Lt2 + Mt4 + St32, D. siamensis (2n=40): Lm2 + Lt6 + Mt4 + St28, and D. melanostictus (2n=42): La2 + Lt12 + Mt4 + St24.